Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan Pada PT. Penerbit Erlangga Cabang Samarinda - Muhtar Sehe; Syachrul Syachrul; Zalfiani Zalfiani (Politeknik Negeri Samarinda, 2020)
Employee performance is the results achieved and the achievements shown by employees that help the company achieve the goals it sets. One way that can be done to print these professional resources is to conduct or include employees in a training. This study aims to analyze the effect of job training on employee performance at PT. Publisher Erlangga Branch Samarinda. Data processing in this study used SPSS 17 for windows software, while for testing using a questionnaire in the validity test and reliability test before the study. The classic assumption test used is the normality test. The hypothesis test used is simple linear regression. After analyzing the data obtained from the respondents, the researcher concludes that job training has an effect on employee performance at PT. Erlangga Publisher, Samarinda Branch.